Role and mechanism of homocysteine in affecting hepatic protein-tyrosine phosphatase 1B - Liu, Ping; Huang, Jin; Zhong, Liangwei (Biochimica et biophysica acta. General subjects, 2019)
Elevated homocysteine is epidemiologically related to insulin resistance. Protein-tyrosine phosphatase 1B (PTP1B) is a negative regulator of insulin signaling. However, the effect of homocysteine on PTP1B remains unclear. S-homocysteinylated PTP1B was identified by LC-ESI-MS/MS. The ability of thioredoxin system to recover active PTP1B from S-homocysteinylated PTP1B was confirmed by RNA interference. To address the mechanism for homocysteine to affect PTP1B activity, we performed 5-IAF insertion, activity assays, Western blotting, co-immunoprecipitation and glucose uptake experiments. The thiol-containing form of homocysteine (HcySH) suppressed phosphorylation of insulin receptor-β subunit, but enhanced PTP1B activity. This phenomenon was partially related to the fact that HcySH promoted PTP1B expression. Although the disulfide-bonded form of homocysteine (HSSH) modified PTP1B to form an inactive S-homocysteinylated PTP1B, HcySH-induced increase in the activities of cellular thioredoxin and thioredoxin reductase, components of thioredoxin system, could recover active PTP1B from S-homocysteinylated PTP1B. Thioredoxin system transferred electrons from NADPH to S-homocysteinylated PTP1B, regenerating active PTP1B in vitro and in hepatocytes. The actions of HcySH were also related with decrease in hepatic glucose uptake. The effect of HcySH/HSSH on PTP1B activity depends, at least partially, on the ratio of active PTP1B and S-homocysteinylated PTP1B. High HcySH-induced an increase in thioredoxin system activity is beneficial to de-S-homocysteinylation and is good for PTP1B activity. Our data provide a novel insight into post-translational regulation of PTP1B, and expand the biological functions of thioredoxin system. •PTP1B is affected by the reduced (HcySH)/oxidized forms (HSSH) of homocysteine.•HcySH reduces phosphorylation of insulin receptor-β subunit/hepatic glucose uptake.•The underlying mechanism is in part related to HcySH-promoted expression of PTP1B.•S-homocysteinylated PTP1B, caused by HSSH, shows aggregation/a decreased activity.•Thioredoxin system may recover the activity of PTP1B from S-homocysteinylated PTP1B.